Podatek rolny a rozwój gospodarstw rolnych - Forfa, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The study presents the construction of agricultural tax is anachronistic. Moreover the article presents it was not achieved the objectives of the reform of 1984. The construction of agricultural tax reduces the role of fiscal functions. Agricultural tax in relation to the revenues achieved from the farms, is much lower. The revenues of community for agricultural tax are at a very low level. It is lack of factors in the structure of agricultural tax that affect to increase the surface area of farms. Flow of workers from agriculture to other sectors of the economy is blocked not only by the taxation system, but also by an insurance scheme.